2004
DOI: 10.1111/j.1525-142x.2004.04041.x
|View full text |Cite
|
Sign up to set email alerts
|

Wing disc development during caste differentiation in the ant Pheidole megacephala (Hymenoptera: Formicidae)

Abstract: The genus Pheidole has three distinct castes in females: queen, major, and minor workers. It has been believed that the larvae of major workers have prominent mesothoracic wing discs, although the minor worker larvae lack them. Here we conducted histological examinations of wing discs during larval development in P. megacephala. We show that all three castes have mesothoracic wing discs, at least in their early stage of the final larval instar, and that the wings degenerate differently in the dimorphic worker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 16 publications
3
63
0
Order By: Relevance
“…In insects, programmed cell death sculpts head morphology in flies (86) and remodels the outer margins of butterfy wings (87). Interestingly, programmed cell death has also been shown to underlie sexual dimorphism and caste differences in insect wing morphology (88)(89)(90), a situation analogous in many respects to what Moczek et al (37,49) have observed with beetle horns.…”
Section: Changes In the Amount Of Horn Resorption During The Pupal Pementioning
confidence: 60%
“…In insects, programmed cell death sculpts head morphology in flies (86) and remodels the outer margins of butterfy wings (87). Interestingly, programmed cell death has also been shown to underlie sexual dimorphism and caste differences in insect wing morphology (88)(89)(90), a situation analogous in many respects to what Moczek et al (37,49) have observed with beetle horns.…”
Section: Changes In the Amount Of Horn Resorption During The Pupal Pementioning
confidence: 60%
“…Here ants already feature prominently as a ''natural'' system for the study of the genetic developmental mechanism behind the skeletomuscular morphogenesis of the winged thorax found in males and gynes, and its suppression during the development of the flightless thorax in workers (e.g., Abouheif and Wray, 2002;Robinson, 2002;Sameshima et al, 2004). These types of developmental studies are already being extended comparatively to the study of ant species in which the reproductive females display ''aberrant'' arrangements in the adult thoracic sclerites, but are nonetheless produced normally during the colony's life cycle (e.g., Baratte et al, 2006).…”
mentioning
confidence: 99%
“…In conclusion, wing development in ergatoids may be regulated in a worker-like and ergatoid-specific manner depending on the forewing/ hindwing development and the developmental stages. As in other ant species (Sameshima et al 2004;Gotoh et al 2005), this degenerating process would be mediated by apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Morphological differences among castes As the larval morphologies of numerous ant species differ markedly depending on developmental fate (Wheeler & Wheeler 1976;Sameshima et al 2004), in M. nipponica, these larvae might be classified as either undifferentiating or differentiating into queens, ergatoids, workers or males on the basis of their morphological differences. Therefore, to examine the allometric differences in larvae destined to be reproductives and workers in alate queen and ergatoid colonies, we conducted morphometric studies on 267 and 234 fixed larvae randomly collected from 15 alate queen and 20 ergatoid colonies, respectively.…”
Section: Methodsmentioning
confidence: 99%